THE INFLUENCE OF COMPENSATION TO EMPLOYEE PERFORMANCE IN FOOD SECURITY AND ANIMAL HUSBANDRY OFFICE - Muammar Kadapi Harahap (Airlangga Journal of Innovation Management, 2021)
Compensation is considered very important tool to increase employee morale in the progress of organization or bureaucracy in a company or institution. By giving any compensation, every employee will have high morale at work. So that the company can achieve the targets that have been set, even more than it should be. Likewise with this study which will look at the effect of compensation on improving employees performance the food security and animal husbandry office in North Sumatra province. Compensation functions as a form of reward received by employees in relation to rewards or for their work performance, both regularly and situational in a company. This research aims to see an effect of compensation in food security and animal husbandry North Sumatra. The process of collecting data in this study uses quantitative methods that are collected based on population and samples at research location. The researcher in this case has determined sample in data collection in accordance with specified problem. As for the population in this study, amounting to 53 people who work in the office for food security and animal husbandry. From the questionnaire given to 53 respondents, each respondent answered 10 questions that had been prepared beforehand. As for this research, it is found that the partial compensation variable has a significant effect on employees performance at Food Security and Animal Husbandry Office of North Sumatra Province. So it can be concluded that compensation is very influential in increasing morale of employee performance and it will have a good impact on activity of food security and animal husbandry in North Sumatra.